Fiscal Policy in a Structural VAR Model for Germany - Christian Breuer; Thiess Buettner (Verein für Socialpolitik, 2010)
This paper examines the effects of fiscal policy measures on GDP and the government budget balance in a structural VAR model. In order to identify expenditure shocks we follow Blachard/Perotti (2002) and assume that government expenditure is partly predetermined in the budget. For the identification of tax policy shocks we exploit changes in tax law in Germany between 1967 and 2008. Our results support significant short term effects of fiscal expansionary policies. In the medium term, however, the model predicts substantial increases in government debt. Applying the model to the recent stimulus programmes in Germany, we find that the stimulus programme had substantial effect on output in the short run.
Keywords: E62; H30; E00; 330; Fiscal policy; tax policy; government spending; structural VAR